2017
DOI: 10.1002/clen.201600210
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of High N2O Emissions from Greenhouse Vegetable Field Soils

Abstract: Vegetable cultivation in China is characterized by high N application rate, multiple cropping, and frequent irrigation, which may have caused high N 2 O emission. However, the N 2 O emission characteristics and the underlying mechanisms responsible for N 2 O emission under high N application rate in the greenhouse vegetable field soils remains largely unknown. Thus, we conducted a field experiment to monitor N 2 O emissions using static chamber and gas chromatography techniques. Meanwhile, an incubation experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This study revealed that urea application alone significantly promoted soil N 2 O emissions. The factors controlling soil N 2 O emissions include soil nitrogen concentration, nitrogentransforming functional microorganisms, appropriate soil temperature, and soil aeration performance [32][33][34][35]. The effect of N fertilizer application on N 2 O emissions was significant and was also verified in this study.…”
Section: Response Of Soil N 2 O Emissions To Bamboo-biochar-based Fer...supporting
confidence: 69%
“…This study revealed that urea application alone significantly promoted soil N 2 O emissions. The factors controlling soil N 2 O emissions include soil nitrogen concentration, nitrogentransforming functional microorganisms, appropriate soil temperature, and soil aeration performance [32][33][34][35]. The effect of N fertilizer application on N 2 O emissions was significant and was also verified in this study.…”
Section: Response Of Soil N 2 O Emissions To Bamboo-biochar-based Fer...supporting
confidence: 69%
“…Reduced N fertilizer application and lowered soil moisture during the growing season explain the differences in soil N 2 O emissions between greenhouse vegetable systems managed by drip fertigation compared with those managed by over fertilization and flood irrigation [8,15,52]. Based on the structure equation modelling analysis, the significant positive direct effect (standardized path coefficients 0.52, p < 0.001, Figure 4) of soil NH 4 + -N concentration on N 2 O emissions indicated that the N 2 O emissions in this drip fertigation systems were primed by the availability of inorganic N, and by nitrification rather than by coupled nitrification-denitrification [52][53][54], as soil moisture levels stayed lower. In contrast, N 2 O emissions were driven by both nitrification and denitrification in the conventional systems managed with over fertilization and flood irrigation [55].…”
Section: Magnitude and Interrelationships Of Soil N 2 O Emissions And...mentioning
confidence: 99%
“…During the WS growing seasons, the mitigation effects on N 2 O emissions of biochar or straw mainly occurred within 10 days after basal fertigation (Figure 3b), when the soil environment condition was conducive to nitrifier and denitrifier activity [28,52]. Firstly, the significant reduction in N 2 O emission fluxes with biochar incorporation compared with DIF is related to its large specific surface and porosity, meaning lower availability of NH 4 + -N and dissolved organic carbon for microbial nitrification and denitrification [38,39].…”
Section: Different Seasonal Responses Of N 2 O Emissions To Biochar O...mentioning
confidence: 99%
“…A comprehensive review of 491 observations from 84 publications revealed that heterotrophic nitrification contributes significantly to NO 3 production, with percentages of 24%, 32%, and 43% in forest, farmland, and grassland soils, respectively [115]. In specific environments like acidic soils found in subtropical forests [116], greenhouse vegetable fields [117], and dairy farms [118], heterotrophic nitrification can even surpass autotrophic nitrification. Unfortunately, current nitrification inhibitors only target autotrophic nitrification, neglecting the heterotrophic aspect.…”
Section: Challenges and Prospectsmentioning
confidence: 99%